Dispensasi Pengadilan Berkaitan Permohonan Perkawinan Dini - Ade Kurniawan (Kyadiren, 2022)
This study aims to examine the various factors that lead to the emergence of early marriage and examine the judge's decision which gives consideration in its determination and grants early marriage in Biak Numfor Regency. The research method used was empirical juridical research method. The research result shows that various factors that cause teenagers' desire to have an early marriage include education, environment, customs, economy, and the individual intention to be immediately separated from his parents and want to live independently. The judge in making a decision of course considers the available evidence, because the evidence encourages the judge's power in making a decision and determination as the legal guideline.